Niños y niñas cuidados : el reconocimiento mutuo en la experiencia de las madres comunitarias antioqueñas (2012)
ABSTARCT: This paper shows the results of research of the category "childminding" in the experience of community mothers at community welfare homes in Antioquia. Method: a qualitative approach with a specific phenomenological-hermeneutical method. In depth interviews and focus groups were also used on 30 community mothers from Antioquia. Results: these mothers consider these children as theirs. They are capable of apprehending them in terms of discourse and indices. They also continue taking care of children even after they leave the community home. Conclusions: when caring for others is a vocation, both community mothers and children recognize each other and reconfigure their own identity permanently. The child-minder job involves a permanent subjective self-transformation exercise which is characteristic of the so-called ethics of self-care.